Evaluation of antibody titers in COVID-19 patients with cerebral or pulmonary symptoms and mild symptoms - Nazanin Joudaki; Samireh Ghafouri; Kowsar Bavarsad; Farbod Farhadi; Marzieh Abbasi Nasab; Sara Afzalzadeh; Hamidreza Moradzadegan; Roya Salehi Kahyesh (Iranian Journal of Microbiology, 2024)
Background and Objectives: This study aimed to compare the production of antibodies in three different groups of patients with COVID-19. These groups included patients with pulmonary and cerebral symptoms, as well as those with mild symptoms. Materials and Methods: Blood samples were collected from 80 patients admitted to COVID-19-specific hospitals. The patients had various forms of SARS-CoV-2 disease, including those with pulmonary symptoms, brain involvement, and those with positive PCR test results but mild symptoms. The enzyme-linked immunosorbent assay (ELISA) technique was used to determine the levels of IgM and IgG antibody titers. Results: The levels of IgM and IgG antibody production differed significantly between groups of patients experiencing pulmonary symptoms and cerebral symptoms, with mild symptom patients also showing differences (P=0.0068), (P=0.0487), (P<0.0001), and (P=0.0120), respectively. Furthermore, there was no significant relationship between IgM antibody secretion and age or pulmonary involvement (P=0.1959). However, there was a direct and significant relationship between age and brain involvement (P=0.0317). Conclusion: The findings of this study revealed that the risk of central nervous system involvement increases with age and that older people have lower antibody levels than younger people. Consequently, strengthening the immune systems of people over the age of 78 during this pandemic through vaccination and nutrition is very effective in reducing mortality in this age group.